La evaluación de confianza en los requisitos de calificación del oficial de cumplimiento - López Rodríguez, Leslie Mayer (2025)
cuador has been managing the necessary legislative changes to adapt to the frontal fight against organizations dedicated to money laundering and terrorist financing, crimes considered as the source that generate or reproduce an illegal economy, capable of feeding criminal finances. Within these changes, relevant requirements have been incorporated for the designation as compliance officer, analyzing the important functions that this officer has in financial institutions, having to increase in the selection processes, the fulfillment of the confidence parameters - polygraph to be able to evaluate their level of credibility. In this context, the general objective of this research was to determine if the evaluation of trust in the qualification requirements of the compliance officer mitigates the risks of corruption in the detection of money laundering in financial institutions in Ecuador. Applying a qualitative approach methodology, we have sought the analysis of current documents that address the figure of the compliance officer. The main conclusion reached is the need to implement mechanisms for the evaluation of trustworthiness within the requirements for the designation of the compliance officer, including the polygraph test.